KAJIAN STRATEGIS PERCEPATAN DAN PENGEMBANGAN FITOFARMAKA UNTUK KESEHATAN MASYARAKAT - Hermawan Saputra; Desrialita Faryanti; Farhan Farhan (Jurnal Delima Harapan, 2022)
Indonesia is a "megabio-diversity" country, the World Conservation Monitoring Center has reported that the territory of Indonesia is an area where many types of medicinal plants are found with the number of plants that have been utilized reaching 2,518 species (EISAI, 1995). Indonesia's wealth of biological resources is a potential resource in the pharmaceutical sector which has not been fully utilized. (Prodisfar, 2021). The purpose of this study is to develop and recommend strategies for accelerating and developing phytopharmaceuticals for public health in Indonesia. The research method is Qualitative Method. The population and sample of the study were conducted by purposive sampling involving informants from across ministries, the pharmaceutical industry, as well as professional organizations in Indonesia, and hospitals. The results of the study show that Indonesia must carry out an acceleration strategy using an intensive strategy (Market Penetration and Product Development and Market Product), while the development strategy is carried out by backward integration, forward integration and horizontal integration as an effort to maintain public health in Indonesia. Suggestions for further researchers, in order to be able to conduct special studies on halal products and pharmacoeconomics for public health.